Increasing Community discourse and Action on GBV prevention in Akai Effa and Idundu, Cross River State - Yta, Edisua Merab; Umukoro, Gloria Mayen; Ekpe, Moses Essien (Universitas Negeri Makassar, 2020)
Gender-Based Violence is an issue of high global concern and has serious implications for every aspect of womenâ€™s lives. The aim of the study was twofold, to increase awareness and knowledge of community members on the contexts in which GBV occurs through the narrative based methodology. It also sought to generate community actions and stem the tide of gender-based violence in Akai Effa and Idundu, Cross River State. The work used a creative narrative based research methodology to explore the contexts in which GBV and inequalities occur. The study had several phases including advocacy visits, production of films, film tours, and the formation of neighbourhood committees. The film â€œWomen of our Landâ€ was a collage of various scenes from different authors produced by DreamBoat Theatre for Development Foundation including; Tess Onwumeâ€™s â€˜The Broken Calabashâ€™ and â€˜The Reign of Wazobiaâ€™, Edisua Ytaâ€™s â€˜Because I am a womanâ€™ and â€˜Wives, mothers and daughtersâ€™ TV, and radio serials, Liwhu Betiang's â€˜The First Stoneâ€™, Data Phidoâ€™s â€˜Rainbow Cityâ€™ and Chris Nwamuoâ€™s â€˜The Substituteâ€™. The film (an enter-educate strategy) was used as a starting point for dialogues in the communities. About three hundred community members were involved in Akai Effa and Idundu and the project ran for six months. Findings identified the following factors as manifestations of gender-based violence in the communities: Domestic violence especially wife battery, sexual abuse, harassment and rape of young girls, restriction placed on women's economic activities, loss of land, assets, and properties, forceful ejections, and young girls denied opportunities to go to school. It is recommended that an extension of project time is essential to allow for adequate behaviour change and stamp out GBV in our communities.